Preface - Gabryś-Barker, Danuta; Wojtaszek, Adam (Theory and Practice of Second Language Acquisition, 2026)
The present issue consists of articles in various areas of SLA and also research in multilingualism. The thematic spread starts with the text related to the sociolinguistic variable of age: "The Age Factor in the Foreign Language Class: What Do Learners Think?" by Simone E. Pfenninger and David Singleton, followed by a study of non-native speaker e-mail communication (Jan Pikhart) and another paper addressing a sociolinguistic variable: "Do Girls Have All the Fun? Anxiety and Enjoyment in the Foreign Language Classroom by Jean-Marc Dewaele et al. The second group of articles begins with the text addressing the issues of multilingualism: "Multilingual Processing Phenomena in Learners of Portuguese as a Third or Additional Language" by Teresa M. Włosowicz, followed by a study of code-switching practices among immigrants in the UK by Katarzyna Ożańska-Ponikwia. The final paper by Beata Grymska represents a more theoretically-oriented perspective delving into the theoretical conceptualizations of language aptitude.